Community-based management of chronic obstructive pulmonary disease in Nepal-Designing and implementing a training program for Female Community Health Volunteers. - Tara Ballav Adhikari; Bishal Gyawali; Anupa Rijal; Abhishek Sapkota; Marieann Högman; Arjun Karki; Torben Sigsgaard; Dinesh Neupane; Per Kallestrup (Public Library of Science (PLoS), 2022)
Chronic obstructive pulmonary disease (COPD) is one of the leading causes of morbidity and mortality in Nepal. Female community health volunteers (FCHVs) have proven effective in the delivery of reproductive, maternal, and child health services in Nepal and recently in the prevention and management of hypertension and type 2 diabetes. Evidence on their roles in COPD management is not yet available. The aim of this study was to develop, implement, and evaluate a training program for FCHVs regarding COPD prevention and management. The training program was part of a cluster-randomized trial of a 12-month intervention to improve COPD outcomes in a semi-urban area of Western Nepal. A six-day workshop consisting of thirty hours of training was developed for FCHVs. Training materials incorporated introduction to COPD, risk factors and symptoms, COPD status assessment guide for FCHVs, guidance on breathing techniques, and exercises for people living with COPD. Pre- and post-test questionnaires were administered to assess the change in knowledge of FCHVs, post training skills assessment followed by semi-structured interviews assessed FCHVs' satisfaction with the training program. The findings of the pre- and post- test assessments showed a significant improvement in FCHVs' COPD-related knowledge from a median (interquartile range) score of 12 (3-16) before to 21 (21-22) (p<0.001) after the training program. The qualitative assessment revealed the feasibility of FCHVs' training on COPD and their acceptability to deliver the intervention package within the community. It also indicated that implementing future training with an extended period and a few days break in-between could enhance the effectiveness. Training of FCHVs in COPD management is feasible and leads to improvement in knowledge. The motivation shown by FCHVs to deliver the intervention could inform and guide community programs and policies for COPD prevention and management in Nepal and similar settings.